An Effective Financial Management Model in Non-Formal Educational Institutions: A Case of Majelis Taklim Kampung Maffaz, Pesantren Maskanul Huffadz - Abdulloh alfarizi, Abdulloh; Wisnu ahmad; Saefullah; Jundullah Wafiq (CV. Kayaswara, 2025)
As a non-formal educational institution, the Majelis Taklim (Islamic study group) plays a strategic role in fostering and empowering the community, particularly in religious, social, and moral aspects. The Majelis Taklim serves not only as a means of religious learning but also as a forum for strengthening social bonds, increasing collective awareness, and fostering spiritual values in daily life. However, the sustainability of this institution depends heavily on effective financial management, which is carried out transparently and accountably. Good financial management will create a sustainable funding system and increase the trust of the congregation and the community in the institution. This study aims to identify the current state of financial management at the Majelis Taklim in Maffaz Village. This study examines the various challenges faced in practice and designs a financial management model that aligns with the characteristics of Islamic boarding school-based non-formal institutions. The research method used is a qualitative approach with a case study method, through interviews, direct observation, and document analysis. The results show that the financial system used is still simple and highly dependent on trust, but has shown positive trends towards transparency and accountability.